Giving current and future generations a real voice: a practical method for constructing sustainability viewpoints in transport appraisal - Cornet, Yannick; Barradale, Merrill Jones; Barfod, Michael Bruhn; Hickman, Robin (European Journal of Transport and Infrastructure Research, 2018)
Decisions to invest in large-scale transport projects typically extend beyond traditional costbenefit analysis. Multi-criteria analysis methods such as multi-actor multi-criteria analysis (MAMCA) have been proposed to assess wider economic effects and long-term environmental impacts from various stakeholder perspectives. However, there is no standard practice for appraising transport projects against sustainable development objectives. In order to give future generations a voice in decisions that will impact them, this paper extends the MAMCA methodology to make various actors and a “sustainability viewpoint” explicit. A dual-approach method for constructing sustainability viewpoints in transport appraisal is proposed. The method juxtaposes an expert-based approach with a principle-based approach. In the former, sustainability experts are asked to prioritise criteria for project assessment. In the latter, criteria weights are calculated based on sustainability theory (“strong” and “weak” sustainability). Together, these viewpoints are intended to inform decision-making. The appraisal of HS2 Phase I, a high-speed rail project in the UK, is used to demonstrate the proposed method. It is found that all three variants of the sustainability viewpoint result in project preferences that are similar to each other, but different from those of other transport professionals. The paper concludes by arguing for the explicit inclusion and triangulation of sustainability viewpoints in transport appraisal on a multi-actor basis. One practical recommendation from the MAMCA process is the need to hire more transport planners with sustainability experience into government planning agencies.